Preliminary study of the antimicrobial activity of Mentha x villosa Hudson essential oil, rotundifolone and its analogues - Arruda,Thúlio. A. (2006)
Essential oils present antimicrobial activity against a variety of bacteria and yeasts, including species resistant to antibiotics and antifungicals. In this context, this work aims at the evaluation of the antimicrobial activity of the essential oil of Mentha x villosa Hudson ("hortelã da folha miúda"), its major component (rotundifolone) and four similar analogues of rotundifolone (limonene oxide, pulegone oxide, carvone epoxide and (+)-pulegone) against strain standards of Staphylococcus aureus ATCC 25923, E. coli ATCC 25922, Pseudomona aeruginosa ATCC 27853, Candida albicans ATCC 76645 and one strain of meticilin - resistant Staphylococcus aureus - MRSA (171c) from human clinic. The method of the diffusion in plates with solid medium was used. The results showed that the oil of Mentha x villosa, rotundifolone, limonene oxide and (+)-pulegone, are similar regarding the antimicrobial activity against the tested strains of S. aureus and C. albicans. All of the products present antimocrobial potential with antibacterial activity for S. aureus ATCC 25923 and antifungal activity for C. albicans ATCC 76645. None of the products presented antimicrobial activity for the strains of E. coli ATCC 25922 and P. aeruginosa ATCC 27853, representatives of the Gram negative bacteria.